Nitrogen (N) for Citrus Trees - Mongi Zekri; Tom Obreza (EDIS)
Nitrogen is the key component in mineral fertilizers applied to citrus groves. N has more influence on tree growth, appearance, and fruit production/quality than any other mineral element. Nitrogen affects the absorption and distribution of practically all other elements, and it is particularly important to the tree during flowering and fruit set. This 3-page fact sheet was written by Mongi Zekri and Tom Obreza and published by the UF Department of Soil and Water Science, July 2013.